Technique, variation, and progression of the rear-foot-elevated split squat - McCurdy, K. (Strength and Conditioning Journal, 2017)
The rear-foot-elevated split squat is a multijoint exercise used to train the lower extremity musculature in all planes. The benefits include prevention of lower extremity injury, improved gait and sport performance, and increased muscle size and strength. With an anterior-posterior stance, the exercise is performed primarily unilaterally.